Supportive Care Needs Among Persons with Prostate Cancer - นพคุณ, ลลิดา; วุทธานนท์, นัทธมน (Nursing Journal CMU, 2019)
Meeting supportive care needs is a crucial factor in reducing life imbalance-caused by the effects of the disease and its treatments-among prostate cancer patients. The objective of this descriptive research was to explore the supportive care needs of persons with prostate cancer admitted at a university hospital between January and June 2017. Purposive sampling was used to select 127 patients. The research instrument used was the Supportive Care Needs in Cancer Patients Thai questionnaire translate by Supan Unjai. Data were analyzed using descriptive statistics. The results revealed that: Participants reported their supportive care needs 23.6% of the total, with the mean score of the supportive care needs were at the low level in psychological needs, patient care and support needs, health system and information needs, and physical and daily living needs ( =1.49; S.D.=0.63; =1.53; S.D.=0.64; =1.59; S.D.=0.61; =1.60; S.D.=0.65 respectively) which accounted for 27.6%, 40.2%, 14.2%, 23.6% respectively. Meanwhile, the mean score of sexual needs was at the moderate level ( =1.67; S.D.=0.61) which accounted for 21.3%. These results could be used as basic information for planning nursing care in order to provide prostate cancer patients with supportive care needs in accordance with the necessity to achieve on overall balanced livelihood.